Southeastern Librarian, Vol. 42, No. 04, Winter 1992 - Curry, Elizabeth; Hughes, Raylynn; Tucker, David; Baughman, Steven A. (The Southeastern Library Association, 1992)
The Southeastern Librarian, Vol.42, No.04, Winter 1992. Periodical.
1 electronic record. 43 pages. Scanned from original document. Contents Include: SELA Officers and Staff- cover verso, State Library Association Officers- cover recto, President's Page- 99, Editor's Page- 100, Steven A. Baughman- SoLINE: Resource Sharing for the Southeaster- 101-104, J. Richard Madaus- Networking: A Statewide Project Perspective- 105-107, Joe Forsee- GOLD: The Georgia Online Database- 109-111, Diana Young- The North Carolina Information Network- 113-116, Southeast Networks: Directory Plus- 117-124, Bulletin Board- 125, Calendar- 134, New & Useful- 126, People- 131, Stateside View- 129-130, State Editors- 133, Guidelines for submission- 98, Membership form- 132
Keywords: Periodicals | Southeastern Library Association